Alfred Müller-Armack and Ludwig Erhard: Social Market Liberalism - Nils Goldschmidt (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik, 2004)
"Soziale Marktwirtschaft" (Social Market Economy) is the economic order that was established in Western Germany after 1945. It is not a precisely outlined theoretical system but more a cipher for a "mélange" of socio-political ideas for a free and socially just society and some general rules of economic policy. It is a decided liberal concept, based on individual freedom and the belief that well-functioning markets and competition lead to economic efficiency and by this, to economic development (or in the case of Germany, recovery) and social improvement. But in sharp distinction to the harmonious Smithian world of the "invisible hand", the "founding fathers" of the post-war economic order in Germany were convinced that the economic system must be guided by an "economic constitution" provided by the state.
Keywords: 330; Soziale Marktwirtschaft; Ordoliberalismus; Wirtschaftswissenschaftler; Persönlichkeiten; Wissenschaft; Deutschland; Müller-Armack Alfred